Development of an exergy diagram for integrated energy systems illustrating the irreversibility along energy paths. (2018) - Saloux, Etienne; Sorin, Mikhail; Teyssedou, Alberto
This paper tackles the development of an exergy diagram, adapted from the heat ( Q )-Carnot factor ( θ ) one, where energy quality factors are given in the ordinate axis while energy terms constitute the abscise axis. Energy and exergy balances are then shown and the nature of irreversibility sources (energy loss, energy potential degradation) is revealed, contrary to traditional Grassman diagrams. In this paper, the graphical construction is extended to integrated energy systems where energy paths are differentiated according to renewable and non-renewable sources. Thus, it permits the electricity use, which is really paid, to be emphasised, and the overall behaviour to be better understood. As well, the diagram is developed to illustrate the results of dynamic analyses by considering environment reference state variations. To this aim, the graphical construction has been applied to individual units and then, step by step, to a solar assisted heat pump using ice storage.